Betrayal Aversion: Evidence from Brazil, China, Oman, Switzerland, Turkey, and the United States: Comment - Bolton, Gary E; Ockenfels, Axel (American Economic Review, 2010)
In a series of binary choice problems, we investigate how a chooser's risk taking changes when others share in their personal risk, either equally or unequally. We find that when the safe option yields inequality, the risky option is taken significantly more often. On the other hand, the inequality resulting from the risky choice does not affect risk taking. We also find that choosers tend to be less risk-averse in a one-person context compared to when the risk also affects the payoff of another. (C72, D81, Z13)